PENERAPAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN KONSUMEN PADA PT ETOS SURYANUSA - Karolus Putra Setiadi; Leonard Adrie Manafe (KALIANDA HALOK GAGAS, 2021)
ABSTRACT: Business sustainability and company goals can be measured by the company's level of service to customer satisfaction. With the recognition of customer satisfaction, it means that the use of products or services can continue and of course the company will get definite and smooth profits and business. The purpose of this study is to determine customer satisfaction is determined by the level of service of the company. Descriptive qualitative research method provides an overview of the results of the analysis that is easily accessible to readers. The research sample consisted of 30 informants who had become consumers of PT Etos Suryanusa. Research data collection was carried out through distributing questionnaires, taking documentation and direct interviews. The results obtained from the research are physical evidence factors, reliability factors and responsiveness factors are important factors in increasing consumer satisfaction. The reliability factor has the most dominant influence on customer satisfaction. Assurance and empathy factors do not have any effect on customer satisfaction, instead they are considered as inhibiting factors for service quality.